Neutrophil extracellular traps in tumor progression of gynecologic cancers - Chen, Hong; Zhou, Ying; Tang, Yaling; Lan, Jianfa; Lin, Chao; Chen, Qionghua; Kuang, Hongying (Frontiers in Immunology, 2024)
This article delves into the intricate interplay between tumors, particularly gynecologic malignancies, and neutrophil extracellular traps (NETs). The relationship between tumors, specifically gynecologic malignancies, and NETs is a multifaceted and pivotal area of study. Neutrophils, pivotal components of the immune system, are tasked with combating foreign invaders. NETs, intricate structures released by neutrophils, play a vital role in combating systemic infections but also play a role in non-infectious conditions such as inflammation, autoimmune diseases, and cancer. Cancer cells have the ability to attract neutrophils, creating tumor-associated neutrophils, which then stimulate the release of NETs into the tumor microenvironment. The impact of NETs within the tumor microenvironment is profound and intricate. They play a significant role in influencing cancer development and metastasis, as well as modulating tumor immune responses. Through the release of proteases and pro-inflammatory cytokines, NETs directly alter the behavior of tumor cells, increasing invasiveness and metastatic potential. Additionally, NETs can trigger epithelial-mesenchymal transition in tumor cells, a process associated with increased invasion and metastasis. The interaction between tumors and NETs is particularly critical in gynecologic malignancies such as ovarian, cervical, and endometrial cancer. Understanding the mechanisms through which NETs operate in these tumors can offer valuable insights for the development of targeted therapeutic interventions. Researchers are actively working towards harnessing this interaction to impede tumor progression and metastasis, opening up new avenues for future treatment modalities. As our understanding of the interplay between tumors and NETs deepens, it is anticipated that novel treatment strategies will emerge, potentially leading to improved outcomes for patients with gynecologic malignancies. This article provides a comprehensive overview of the latest research findings on the interaction between NETs and cancer, particularly in gynecologic tumors, serving as a valuable resource for future exploration in this field.